Common tern Sterna hirundo breeding population - Denac, Damijan (Acrocephalus, 2002)
A colony of Common Terns Sterna hirundo and Black-headed Gulls Larus ridibundus formed in 1981 in the wastewater basins of the sugar factory in Ormož. From than on, the colony has been monitored regularly by direct counting. The site was flooded in 1994 and, in 1995 and 1996, Common Terns andBlack-headed Gulls did not breed. In 1997> the first artificial breeding raft (surface area 12.5 m2) was placed, followed in 1998 and 2001 by additional rafts (14 m2 and 96 m2, respectively). All rafts were placed with the intention of preserving the Common Tern, since this species is highly endangded in Slovenia. As a result, the biggest mixed Common Tern and Black-headed Gull colony in Slovenia has been established on the artificial brecding rafts. In 2002, 64 pairs of Common Tern and 113 pairs of Blackheaded Gull bred on rafts, amounting to 45% and 50% respectively of the Slovene breeding population. Black-headed Gulls started to breed in higher numbers on the largest rafts, placed in 2001, and, for that reason, the percentage of Terns breeding on the rafts decreased. In 2000 all the Terns, but in 2001 only80% of those in the basins were breeding on rafts. It is most probable that the bigger rafts, with special breeding structures for Common Terns, weremore attractive for Black-headed Gulls. Obviously they liked thc heterogeneous raft surface, because they built their nests on the breeding structures planned to increase the breeding success of Common Terns.
Keywords: Birds; Ekosistem; Gnezdenje živali; Ecosystem; bird; Nesting Behavior; Ptice; gnezdenje; čigre